Nitric Oxide-cGMP Signaling: Its Role in Cell Junction Dynamics During Spermatogenesis - Mruk, Dolores D.; Sarkar, Oli; Mathur, Premendu P. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2008)
During spermatogenesis, development of spermatogonia into elongated spermatids takes place in the seminiferous epithelium of the adult mammalian testis. Specifically, post-meiotic germ cell maturation occurs in a unique microenvironment sequestered from the systemic circulation by the blood-testis barrier (BTB), which is formed by adjacent Sertoli cells. Therefore, an intact BTB, as well as stable Sertoli-germ cell adhesion, are important criteria for successful spermatogenesis. To date, numerous factors have been shown to influence spermatogenesis, and among them is the well-studied nitric oxide (NO)/guanosine 3',5'-cyclic monophosphate (cGMP) signaling cascade. The enzymes of this pathway, namely nitric oxide synthase, soluble guanylate cyclase and cGMP-dependent protein kinase, have all been shown to regulate cell junctions in the testis. Likewise, recent findings have shown that this signaling cascade also plays a critical role in the regulation of Sertoli-germ cell adhesion. In this mini-review, we briefly discuss the regulatory role of each protein component of the NO/cGMP pathway in the context of testicular junction dynamics, as well as their importance in fertility and male contraception.
Keywords: nitric oxide signaling pathway